Development of mathematics learning media for lessons related to pyramids using reflective pedagogy paradigm - Rosevita Melati; Haniek Sri Pratini (International Journal of Trends in Mathematics Education Research, 2022)
At schools, many teachers generally applied a conventional way of teaching mathematics. Students were only required to achieve cognitive learning success. This study aimed to develop mathematics learning media for lessons related to pyramids using the Reflective Pedagogical Paradigm (RPP) and Van Hiele theory, including the development steps and student and teacher responses to the learning process. The researchers used the research and development procedures by Borg and Gall that include (1) Preliminary studies; (2) Planning Research; (3) Design Development; (4) Limited Trial; (5) Revision of Limited Field Test Results. The learning tools developed were syllabus, lesson plans, modules, worksheets, formative tests, and attitude assessments. The data collection techniques used were observation, distributing questionnaires, interviews, and tests. Based on the validation results, the learning media got 4.19, thus categorized as "good," and students' response to the learning process reached 128.23, thus categorized as "good" as well. Students and teachers carried out learning happily and actively.